2020
DOI: 10.1101/2020.03.23.003756
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DrosophilaActivin signaling promotes muscle growth through InR/dTORC1 dependent and independent processes

Abstract: The Myostatin/Activin branch of the TGF superfamily acts as a negative regulator of mammalian skeletal muscle size, in part, through downregulation of insulin/IGF-1 signaling.Surprisingly, recent studies in Drosophila indicate that Activin signaling acts as a positive regulator of muscle size. In this study, we demonstrate that Drosophila Activin signaling positively regulates the InR/dTORC1 pathway and the level of MHC, an essential sarcomeric protein, via promoting the transcription of Pdk1 and Akt1. Enhanc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 95 publications
(178 reference statements)
0
5
0
Order By: Relevance
“…Intriguingly however, we find that loss of Actβ , another ligand that signals through Babo and dSmad2, results in a smaller muscles ( Moss-Taylor et al, 2019 ) contrary to that produced by loss of vertebrate Mstn and various other vertebrate Activin family members. Recent data has shown that DrosophilaActβ is the only Activin-like ligand that affects muscle growth, and it does so, in part, by regulating Insulin/Tor signaling in the opposite direction compared to vertebrates ( Kim and O’Connor, 2020 ). Thus, in Drosophila the Myo/Activin pathway promotes muscle growth while in vertebrates it inhibits muscle growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly however, we find that loss of Actβ , another ligand that signals through Babo and dSmad2, results in a smaller muscles ( Moss-Taylor et al, 2019 ) contrary to that produced by loss of vertebrate Mstn and various other vertebrate Activin family members. Recent data has shown that DrosophilaActβ is the only Activin-like ligand that affects muscle growth, and it does so, in part, by regulating Insulin/Tor signaling in the opposite direction compared to vertebrates ( Kim and O’Connor, 2020 ). Thus, in Drosophila the Myo/Activin pathway promotes muscle growth while in vertebrates it inhibits muscle growth.…”
Section: Discussionmentioning
confidence: 99%
“…TGFβ mutants: myo 1 , Actβ 80 , daw 11 , dSmad2 F4 are described previously ( Awasaki et al, 2011 ; Peterson and O'Connor, 2013 ; Serpe and O'Connor, 2006 ; Zhu et al, 2008 ). The new myo CR2 allele is described in Kim and O’Connor, 2020 . Isoform miRNA lines for babo and myo-GAL4 are described previously ( Awasaki et al, 2011 ).…”
Section: Methodsmentioning
confidence: 99%
“…Proper growth of muscles is dependent on ILP signalling. Research by Demontis and Perrimon (2009) and Kim and O’Connor (2021) showed that different components of ILP signalling may be important for the morphological properties (width, thickness, length) and ploidy of insect muscles. The results of these studies showed that the lack of ILP-dependent inhibition of the transcription factor FOXO led to a decrease in the size of D. melanogaster muscles ( Demontis and Perrimon, 2009 ).…”
Section: Metabolic Processes Regulated By Ilpsmentioning
confidence: 99%
“…Similar to its vertebrate homologues, Myc is a central regulator of the growth and proliferation of many cell types, including myocytes ( Gallant, 2013 ). Additionally, research carried out by Kim and O’Connor (2021) showed the importance of ILP signalling in the regulation of muscle growth in insects. The authors confirmed that Activin signalling promotes the growth of D. melanogaster muscles by positive regulation of the insulin receptor IR/TORC1 pathway and the level of Myosin heavy chain (Mhc) by increasing pdk1 and akt1 expression, genes encoding phosphoinositide-dependent kinase 1 and Akt kinase ( Gallant, 2013 ).…”
Section: Metabolic Processes Regulated By Ilpsmentioning
confidence: 99%
“…Insulin signaling in larval muscles is regulated by other signaling pathways including the TFG-β/Activin signaling pathway ligand Activin-β. Activin-β positively regulates insulin signaling and is required for proper muscle geometry and sarcomere protein level (Kim and O'Connor, 2020). While these studies show the importance of insulin signaling in proper muscle size and structure, whether insulin signaling in the muscle alters levels of stored glycogen locally or globally is unknown.…”
Section: The Skeletal Muscle Modulates Insulin Signalingmentioning
confidence: 99%